Association of sexual risk behaviour with previous HIV testing among voluntary HIV counselling and testing clients in Kigali, Rwanda. (December 2016) - Stalter, Randy; Chen, Mario; Uwizeye, Glorieuse; Mutunge, Elise; Ahayo, Anita; Mugwaneza, Placidie; Shumbusho, Fabienne; Wesson, Jennifer
With increased coverage of voluntary HIV counselling and testing (VCT) in Rwanda and a greater focus on repeat testing of key populations, it is important to understand whether the right clients are returning for repeat testing and if repeat testing is effective at reducing risk. We assessed the association between repeat testing and recent sexual risk behaviours among 1852 first time or repeat HIV testing clients in Kigali who had had sex, using data from a cross-sectional survey. Repeat testing was associated with being female, older and type of occupation. Multivariable analyses indicate that individuals who tested for HIV 1–2 times (aOR = 1.52, 95% CI: 1.08, 2.15) and 3+ times (aOR = 1.51, 95% CI: 1.06, 2.17) previously were more likely to report recent unprotected sex. Those with 3+ previous tests were more likely to have recently had multiple sexual partners (aOR = 2.19, 95% CI: 1.22, 3.92). However, a significant decrease in HIV prevalence is shown as individuals receive more HIV tests in their lifetime ( p < 0.001). These findings show that individuals who report high-risk behaviours are returning for repeat tests. However, VCT may not be successful at addressing certain sexual risk behaviours. Therefore more intensive counselling or additional HIV prevention services may be needed.